Sustainable Implementation of Physician-Pharmacist Collaborative Clinics for Diabetes Management in Primary Healthcare Centers: A Qualitative Study - Jie Xiao; Shuting Huang; Qing Wang; Shenglan Tan; Lei Chen; Haiyan Yuan; Daxiong Xiang; Bikui Zhang; Xia Li; Yan Guo; Haiying Huang; Qun Li; et al. (Springer, 2024)
Abstract Background Although physician-pharmacist collaborative clinics for diabetes management have been shown to be effective and cost-effective worldwide, there is limited understanding of the factors that influence their sustainable implementation. This study aims to identify the associated factors and provide sustainability strategy to better implement physician-pharmacist collaborative clinics for diabetes management in primary healthcare centers in China. Methods A sample of 43 participants were participated in face-to-face, in-depth, semi-structured interviews. Consolidated Framework for Implementation Research was used to identify facilitators and barriers to implementing physician-pharmacist collaborative clinics for diabetes management in primary healthcare centers, and to explore discriminating factors between low and high implementation units. A sustainable strategy repository based on dynamic sustainability framework was established to inform further implementation. Results This study demonstrated that clear recognition of intervention benefits, urgent needs of patients, adaptive and tailored plan, highly collaborative teamwork and leadership support were the major facilitators, while the major barriers included process complexity, large number and poor health literacy of patients in primary areas, inappropriate staffing arrangements, weak financial incentives and inadequate staff competencies. Six constructs were identified to distinguish between high and low implementation units. Sixteen strategies were developed to foster the implementation of physician-pharmacist collaborative clinics, targeting Intervention, Practice setting, and Ecological system. Conclusion This qualitative study demonstrated facilitators and barriers to implementing physician-pharmacist collaborative clinics for diabetes management in primary healthcare centers and developed theory-based strategies for further promotion, which has the potential to improve the management of diabetes and other chronic diseases in under-resourced areas.